Isoliensinine suppressed gastric cancer cell proliferation and migration by targeting TGFBR1 to regulate TGF-β-smad signaling pathways - Hu, Jinda; Dai, Shangming; Yuan, Mengqin; Li, Fengjiao; Xu, Shuoguo; Gao, Lichen (Frontiers in Pharmacology, 2024)
Background: Gastric cancer (GC) ranks as the fifth most prevalent cancer globally, and its pronounced invasiveness and propensity to spread provide significant challenges for therapy. At present, there are no efficacious medications available for the treatment of patients with GC. Isoliensinine (ISO), a bisbenzylisoquinoline alkaloid, was isolated from Nelumbo nucifera Gaertn. It possesses anti-tumor, antioxidant, and other physiological effects. Nevertheless, there is currently no available study on the impact of ISO on GC, and further investigation is needed to understand its molecular mechanism. Methods: ISO target points and GC-related genes were identified, and the cross-target points of ISO and GC were obtained. We then examined cross-targeting and found genes that were differentially expressed in GCs. Kaplan-Meier survival curves were used to screen target genes, and the STRING database and Cytoscape 3.9.1 were used to construct protein-protein interactions and drug-target networks. In addition, molecular docking studies confirmed the interactions between ISO screen targets. Finally, in vitro tests were used to establish the impact of ISO on GC cells. Results: Through bioinformatics research, we have identified TGFBR1 as the target of ISO in GC. In addition, we noticed a substantial inhibition in GC cell proliferation, migration, and invasion activities following ISO treatment. Moreover, we noticed that ISO treatment effectively suppressed TGF-β-induced epithelial-mesenchymal transition (EMT) and activation of the TGF-β-Smad pathway. Furthermore, we discovered that siTGFBR1 nullified the impact of ISO on TGF-β-triggered migration, invasion, and activation of the TGFβ-Smad pathway. Conclusion: Our research suggests that ISO specifically targets TGFBR1 and regulates the TGF-β-Smad signaling pathway to suppress the proliferation and migration of GC cells.